Green Economic Growth: A Global Analysis of Fiscal Expenditures, Institutional Quality, and Stock Markets - Putri, Icha Aulia; Mushfiroh, Luluk; Hwihanus, Hwihanus (Indonesian Journal Publisher, 2024)
Green economic growth is the main focus in achieving sustainable development throughout the world. This study aims to conduct a global analysis of fiscal spending, institutional quality, and stock markets in relation to green economic growth. Through a holistic approach, this research explores the complex relationship between these three factors and their impact on sustainable economic growth. By considering various relevant variables and indicators, this study provides an in-depth understanding of the factors influencing the transition to a green economy. Well-directed fiscal spending can encourage investment in green technologies and green infrastructure, while good institutional quality ensures effective and fair policy implementation. Additionally, the stock market plays an important role in providing capital to companies focused on green innovation. It is hoped that the results of this analysis will provide valuable insights for policy makers, economic practitioners and other stakeholders in designing sustainable and environmentally friendly economic development strategies. The findings of this study show that synergy between prudent fiscal policy, strong institutions, and dynamic stock markets is critical to driving green economic growth. Thus, this study has the potential to make a significant contribution to advancing the sustainable development agenda at the global level. The resulting conclusions can form the basis for strategic decision-making that supports the transition to a green economy, as well as help direct investment and public policy in a more sustainable direction.